PERSEPSI TERHADAP KEHARMONISAN KELUARGA DAN KESTABILAN EMOSI DENGAN PERILAKU AGRESIF PADA REMAJA - Rezki Yudiyasiwi, Feslika; Putu Shanti, Luh (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
This research aims to examine the relationship between perceptions of family harmony and emotional stability with aggressive behavior in adolescents at SMP Negeri 2 Jatiwangi. The population of this study includes male and female students at SMP Negeri 2 Jatiwangi, with a sample size of 314 students selected using cluster random sampling. The measurement tools in this study consist of three scales: the aggressive behavior scale with a reliability coefficient of 0.927, the perception scale of family harmony with a reliability coefficient of 0.934, and the emotional stability scale with a reliability coefficient of 0.762. Data analysis techniques involve multiple regression analysis and partial correlation. The results of hypothesis testing indicate a significant negative relationship between perceptions of family harmony and emotional stability with aggressive behavior in adolescents at SMP Negeri 2 Jatiwangi, with an R value of 0.468 and an F value of 43.655, and a significance level of 0.000 (p<0.01).